The THE POTENCY OF CINNAMON (Cinnamomum burmanni Blume) LEAF EXTRACT AS A BIOPRESERVATIVE AGENT FOR FOOD SAFETY OF SATE LILIT: - - Ida Bagus Gede Darmayasa; Yan Ramona; Anak Agung Ketut Darmadi; I Wayan Suanda; Ni Luh Hani; Kalidas Shetty (SEAMEO BIOTROP, 2024)
ARTICLE HIGLIGHTS- Cinnamon leaf extract combats E. coli in traditional Balinese food.- Natural preservative reduces harmful pathogens in sate lilit.- Cinnamon extract offers a safer alternative to synthetic preservatives.- Active compounds in cinnamon leaves inhibit bacterial growth.- Effective biopreservative for enhancing food safety and quality. ABSTRACTEscherichia coli O157:H7 contamination of the meat used in preparing sate lilit, a favorite traditional food in Bali, Indonesia, has been a great concern for both local people and foreigners. Although C. burmanni has been included in its spice ingredients, active compounds that play a significant role in this pathogen have limitedly been elucidated. The main objectives of this research were to investigate the potency of this plant to control contaminants and elucidate possible compounds that prevent such contaminants by applying the disk diffusion method and LCMS analysis, respectively. The results showed that the leaf extract of this plant inhibited the in vitro growth of E. coli O157:7, with minimal inhibitory concentration (MIC) and LC50 values of 4% and 2.59%, respectively. The LCMS analysis chromatogram showed that the plant extract's most active fraction produced nine peaks, representing nine possible active compounds. Among those, three compounds (Azoxystrobin, Stigmatellin Y, and 2-arachidonoyl glycerol) were suspected of contributing to control contamination, especially by E. coli O157:H7.